Avoid the trap: Targeting PARP1 beyond human malignancy. Issue 4 (15th April 2021) - Kim, Chiho; Chen, Chuo; Yu, Yonghao
Summary: PARP1 is a poly(ADP-ribose) polymerase (PARP) enzyme that plays a critical role in regulating DNA damage response. The main enzymatic function of PARP1 is to catalyze a protein post-translational modification known as poly(ADP-ribosyl)ation (PARylation). Human cancers with homologous recombination deficiency are highly sensitive to PARP1 inhibitors. PARP1 is aberrantly activated in many non-oncological diseases, leading to the excessive NAD + depletion and PAR formation, thus causing cell death and tissue damage. PARP1 deletion offers a profound protective effect in the relevant animal models. However, many of the current PARP1 inhibitors also induce PARP1 trapping, which drives subsequent DNA damage, innate immune response and cytotoxicity. This minireview provides an overview of the basic biology of PARP1 trapping, and its implications in disease. Furthermore, we also discuss the recent development of PARP1 PROTAC compounds, and their utility as "non-trapping" PARP1 degraders for the potential amelioration of non-oncological diseases driven by aberrant PARP1 activation. Graphical abstract: Abstract : PARP1 inhibitors induce PARP1 trapping, thus they are less useful for the treatment of ischemia reperfusion injury and certain types of neurodegenerative diseases. Here, Kim et al. discuss the recent development of PAPR1 degraders, and how these compounds could be used to target PARP1 for the amelioration of non-oncological diseases.